2021
DOI: 10.1088/1741-2552/ac2bb8
|View full text |Cite
|
Sign up to set email alerts
|

Wireless microelectrode arrays for selective and chronically stable peripheral nerve stimulation for hindlimb movement

Abstract: Objective. Maximizing the stability of implanted neural interfaces will be critical to developing effective treatments for neurological and neuromuscular disorders. Our research aims to develop a stable neural interface using wireless communication and intrafascicular microelectrodes to provide highly selective stimulation of neural tissue. Approach. We implanted a wireless floating microelectrode array into the left sciatic nerve of six rats. Over a 38 week implantation period, we recorded stimulation thresho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
0
5
1
Order By: Relevance
“…Interestingly, we did not observe any obvious trend or relationship between motor recruitment thresholds (I th reported in [12]) and either E mc or V acc for the electrodes. Suggesting that the changes in stimulation-evoked limb movement over time that were recorded in parallel to this study were not directly caused by changes in the electrodes.…”
Section: Discussioncontrasting
confidence: 51%
See 3 more Smart Citations
“…Interestingly, we did not observe any obvious trend or relationship between motor recruitment thresholds (I th reported in [12]) and either E mc or V acc for the electrodes. Suggesting that the changes in stimulation-evoked limb movement over time that were recorded in parallel to this study were not directly caused by changes in the electrodes.…”
Section: Discussioncontrasting
confidence: 51%
“…Increasing electrode surface area from 2000 µm 2 to 3000 µm 2 would mean additional exposure (removal of insulation) of approximately 30 µm along the length of the iridium wire tip, and we expect this increase would not notably decrease selectivity of neural stimulation with the penetrating microelectrode array. Additional information on selectivity of stimulation within this study can be found in [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over a 9.5-month period, the researchers implanted a WFMA into each of 6 rats' left sciatic nerves and observed that a combination of wireless communication and a lowprofile neural interface permitted very steady motor recruitment thresholds and fine motor control in the hind limb. The groundwork has been laid for the development of a visual brain prosthesis in the future (78). Clinical trials in humans are now ongoing (ClinicalTrials.gov Identifier: NCT04634383).…”
Section: Intracortical Visual Prosthesis (Icvp) Projectmentioning
confidence: 99%